Multidimensional digital branding model of intangible cultural heritage – example of Croatian lace making - Ražov, Antonija; Krajnović, Aleksandra; Medić, Ivan (Oeconomica Jadertina, 2026)
Heritage economics is an underdeveloped scientific field. Furthermore, with the growing awareness of the importance of valorization and preservation of cultural heritage as an essential feature of the cultural and national identity of each country, the question arises of how to brand elements of cultural heritage, especially for new marketing generations. The problem of insufficient visibility and inadequate branding of heritage has been observed especially when it comes to intangible heritage, which is also the subject of research in this paper. Namely, it seems that marketing efforts in branding heritage have so far been made primarily by UNESCO and its list of protected cultural goods, but elements at the level of national protection and promotion often remain in the shadows, which is also a problem in the Republic of Croatia. The paper explores the branding model of Croatian lace-making, given the fact that in 2009 this traditional Croatian skill was inscribed on UNESCO's Representative List of the Intangible Cultural Heritage of Humanity under the title Lace-making in Croatia. The model presented by the authors in the paper represents a platform according to which elements of intangible cultural heritage that have not reached the level of UNESCO protection, but are protected at the national level, can be branded. The authors' model proposes a multidimensional model of branding Croatian lace-making, with special emphasis on digital technologies. Methodologically, the research was carried out by combining the Delphi method and brainstorming within the author's team of this paper and research through a focus group of full-time students at the undergraduate study of management at the Department of Economics of the University of Zadar. Using these methods, a 4-D model of branding Croatian lace-making was created, as well as a multidimensional model of branding Croatian lace, which are presented in the paper. As a successful case study, and related to the topic of the research - lace-making, a brief review is also given of the lightning-fast increase in the popularity of lace and lace products that was caused among all generations by the Croatian representative at the world-famous Eurosong 2024 Festival, Marko Purišić - Baby Lasagna. At the end of the paper, the authors provide practical implications and guidelines for further research.
Keywords: economics of cultural heritage, branding of cultural products, marketing of intangible heritage elements, lace making, lace making in Croatia, digital branding, Baby Lasagna phenomenon